New General Split Feasibility Problems in Hilbert Spaces: Kanokwan Sitthithakerngkiet, Waraporn Donsungpri - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, we establish the iterative algorithm for finding the solution of a general split feasibility problem (GSFPg) and show that the proposed algorithm converges strongly to solution of (GSFPg). Moreover, some numerical examples are presented to confirm our results.